Burnout Syndrome and Lifestyle Among Primary School Teachers: A Czech Representative Study - Ptáček, Radek; Vnukova, Martina; Raboch, Jiri; Smetackova, Irena; Sanders, Edel; Svandova, Lucie; Harsa, Pavel; Stefano, George B (Medical science monitor, 2019)
BACKGROUND Burnout is a state of vital exhaustion that is manifested on physical, cognitive, and emotional levels. Teachers work in a field where they are exposed daily to high job-related stressors, which can result in job change, a higher rate of unhappiness, and even earlier retirement. This study explored the relationship between job stressors, lifestyle, and burnout. MATERIAL AND METHODS Descriptive statistics were used to explore the burnout levels, together with t tests to compare between men and women, and regression analysis was performed to explore the relationship between the rates of burnout and lifestyle. RESULTS The overall sample size was 2394 teachers from primary schools. While males had higher emotional burnout, females reported higher physical burnout rates. We found that higher income was associated with less burnout, and a healthier lifestyle is associated with lower burnout rates. Teachers who take time for family and personal interests have significantly lower rates of burnout than those that do not. CONCLUSIONS Based on our results, we propose that teachers should be informed about the risk of burnout. We found that some teachers reported they do not know what burnout syndrome is. The primary aim should be to increase awareness. In fact, burnout is a major threat to those who are perfectionists and who tend to work overtime.
Keywords: Regression Analysis; Syndrome; Male; lidé středního věku; Life Style; duševní vyhoření; Humans; Middle Aged; senioři; Czech Republic; Česká republika; mužské pohlaví; Female; regresní analýza; mladiství; Aged; syndrom; učitelé; ženské pohlaví; mladý dospělý; Adult; Young Adult; Adolescent; dospělí; lidé; životní styl; Burnout, Psychological; School Teachers